Manuel Ribeiro Rocha: an abolitionist avant la lettre? - Carvalho Franca, Jean Marcel [UNESP]; Ferreira, Ricardo Alexandre [UNESP] (Univ Coimbra, Fac Letras, 2015)
In 1830, the Irish reverend Robert Walsh (1772-1852), a cultured and worldly man who spent a few brief months in Brazil as a member of the Committee of the Society for the Abolition of Slavery, wrote this in his book Notices of Brazil: Although the Portuguese were the first Europeans to enslave negros, one must do them justice by emphasizing that they are also those among the first Europeans who placed themselves against trafficking. In 1758, Manuel Ribeiro Rocha, a friar, published a work in Lisbon entitled Etiopia resgatada (Ethiopia Rescued) or Africa redimida (Africa Redeemed), a work that caused a considerable sensation at the time. Little did Reverend Walsh know that his discrete and imprecise note about the work of an obscure 18th century enlightened Portuguese man would give rise to a vast fortune, critically-speaking, in Brazilian historiography, despite the book's small circulation, the absence of re-editions and scant news about the author. But what book, finally, was this? Who was its author, the priest Manuel Ribeiro Rocha? Where did he live and where was he schooled? What other written records have been left to us about this priest? To what cultural world does his work refer? We would be facing some kind of precursor of abolitionism in Portuguese?
Keywords: Manuel Ribeiro Rocha; Colonial culture; Abolitionism